2002
DOI: 10.1206/0003-0090(2002)270<0001:nabftv>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Northern Adriatic Bryozoa From the Vicinity of Rovinj, Croatia

Abstract: One hundred six species of Bryozoa collected from the northern Adriatic in the vicinity of Rovinj, Croatia, are distributed among the orders Ctenostomata (8 species), Cheilostomata (79 species), and Cyclostomata (19 species). Ctenostomes are underrepresented in the collections relative to the two orders with calcified colonies. Five of the cheilostome species are new: Hagiosynodos hadros n. sp., Schizomavella subsolana n. sp., Cellepora adriatica n. sp., Celleporina siphuncula n. sp., and Rhynchozoon revelatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 79 publications
13
100
2
4
Order By: Relevance
“…Examination of type specimens has revealed that the holotype of W. edmondsoni is synonymous with W. subtorquata, and that two species previously synonymised under W. subtorquata and W. subovoidea belong to distinct species: Watersipora atrofusca (Busk, 1856) and Watersipora subatra (Ortmann, 1890 The lack in Watersipora of diagnostic structures such as avicularia and ooecia that are often used in cheilostome taxonomy has led to the use of morphological and morphometric characters of the frontal shield, orifice and operculum to identify species in the genus (Soule & Soule 1975;Seo 1999;Ryland et al 2009). Six species-W. cucullata, W. arcuata, W. atrofusca, W. bidentata, W. nigra and W. platypora-have an orifice with the sinus almost square or rectangular in shape (see Okada & Mawatari 1937;Banta 1969a;Seo 1999), while W. complanata is distinct in having an orifice with a straight proximal edge lacking a sinus (Hayward & McKinney 2002). The other six species-W. aterrima, W. mawatarii n.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of type specimens has revealed that the holotype of W. edmondsoni is synonymous with W. subtorquata, and that two species previously synonymised under W. subtorquata and W. subovoidea belong to distinct species: Watersipora atrofusca (Busk, 1856) and Watersipora subatra (Ortmann, 1890 The lack in Watersipora of diagnostic structures such as avicularia and ooecia that are often used in cheilostome taxonomy has led to the use of morphological and morphometric characters of the frontal shield, orifice and operculum to identify species in the genus (Soule & Soule 1975;Seo 1999;Ryland et al 2009). Six species-W. cucullata, W. arcuata, W. atrofusca, W. bidentata, W. nigra and W. platypora-have an orifice with the sinus almost square or rectangular in shape (see Okada & Mawatari 1937;Banta 1969a;Seo 1999), while W. complanata is distinct in having an orifice with a straight proximal edge lacking a sinus (Hayward & McKinney 2002). The other six species-W. aterrima, W. mawatarii n.…”
Section: Discussionmentioning
confidence: 99%
“…It has been subsequently found in many European seas (DYRYNDA et al, 2000). The alien status of Bugula fulva is supposed based on its patchy occurrence nearly restricted to harbours (HAYWARD & MCKINNEY, 2002).…”
Section: Miscellaneous Invertebrates In the Adriatic Seamentioning
confidence: 99%
“…While the distribution of M. buski was restricted in the Gulf of Mexico, M. cereoides was recorded in the Atlantic, the Mediterranean, Europe, and North Africa. It was found on Posidonia oceanica rhizomes collected from Cyprus coastal waters (Koçak et al, 2002) and it is probably considered as an endemic species (Hayward and McKinney, 2002).…”
Section: Resultsmentioning
confidence: 99%